Nanoscale analysis of multiwalled carbon nanotube by tip-enhanced Raman spectroscopy. (April 2016) - Chaunchaiyakul, Songpol; Yano, Takeshi; Khoklang, Kamonchanok; Krukowski, Pawel; Akai-Kasaya, Megumi; Saito, Akira; Kuwahara, Yuji
Abstract: The relationship between the 2D and G band intensities and the number of walls of a multiwalled carbon nanotube was investigated by tip-enhanced Raman spectroscopy, which enables spatial resolution of nanometer order. The 2D band to G band integrated intensity ratio was found to be sensitive to the number of carbon nanotube walls. Furthermore, the 2D band intensity was enhanced by the intertube interaction between carbon nanotubes. This phenomenon can be explained by quantum interference between Raman scattering paths resulting from the strong interaction between carbon nanotube walls.